China potencia económica y comercial: una mirada desde el Perú - Fairlie Reinoso, Alan (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
This paper analyzes the role of China in the current world situation and its position in the global economy. It also describes China’s foreign policy, and its participation in the international forums. The characteristics of the bilateral trade relationship with Peru are examined, and the investments from China are discussed, including the key sectors that involves and itsimplications in national economy.

El presente trabajo analiza el rol de China en la nueva coyuntura mundial y su posicionamiento en la economía global. Asimismo, la política exterior de China, y participación en otros foros internacionales. Luego, se examina las características de la relación bilateral comercial con Perú. Se discute la inversión procedente de China, los sectores claves a los quese dirige y sus implicancias.
China as economic and commercial power: A a view from Peru
Keywords: China; Trade; Investment; International Forums; Trade Policy; Foreign Policy; Bilateral Relations; Peru; China; Comercio; Inversión; Foros Internacionales; Política Comercial; Política Exterior; Relación Bilateral; Perú; https://purl.org/pe-repo/ocde/ford#5.09.01